Engaging with Stakeholders of the Technological Future through Prophetic Dialogue: A Catholic Perspective - Le Duc, Anthony (JURNAL LEDALERO, 2024)
This paper explores the role of the Catholic Church in the cognitive revolution driven by science and digital technology, and its engagement with stakeholders in technological development. Using qualitative analysis, it proposes a framework of “prophetic dialogue” from the Catholic perspective to effectively engage with stakeholders. The framework is developed from the teachings of the Catholic Church on mission engagement, and the ideas of theologians Stephen Bevans and Walter Bruggemann, focusing on mission, prophetic dialogue, and prophetic communication. Analyzing the framework in the digital context reveals that prophetic dialogue is an appropriate and effective approach for engaging with stakeholders, including innovators, policymakers, and consumers. By employing prophetic dialogue, the Church can shape the future of technology while safeguarding against potential negative consequences. The paper highlights the Church’s proactive role in influencing technological development and offers insights for other religious stakeholders in navigating the challenges and opportunities of the digital future.Keywords: prophetic dialogue, digital technology, digital future, stakeholders, religious communication